Performance Analysis of WDM-PON Architecture for Wireless Services Distribution in Future Aircraft Networks - Coelho, Diogo Vieira Nogueira (2013)
In this work, an in-depth analysis concerning the transmission performance of IEEE802.11g/n (Wi-Fi) signals in a WDM-PON system is presented. It is considered that the optical/electrical transceivers are based on low-cost 850 nm VCSELs and PIN photodiodes. System modelling includes the impact of noise generated in the optical path, such as relative intensity noise (RIN), shot noise, photodetector thermal noise, clipping and intermodulation distortion. An analytic analysis based on Volterra series is conducted and mathematical expressions for both the EVM and SNR are derived. The theoretical analysis is also compared with experimental results. Among several conclusions, it is observed that the laser intermodulation distortion, clipping and RIN are the most relevant factors.